"Kick it like Ronaldo": a cross-sectional study of focus of attention effects during learning of a soccer knuckle ball free kick technique - Schwab, S.; Rein, R.; Memmert, D. (German Journal of Exercise and Sport Research, 2019)
The aim of this study was to investigate whether soccer free kick training improves the knuckle ball technique of adolescent and adult male soccer players after a three week training period using either internal or external focus of attention instructions. Much evidence has been gathered in the literature showing that an external focus of attention (i.e., focus on the movement effects) is more effective than an internal focus (i.e., focus on the movements themselves) during learning. In the present study, 56 soccer players (20 adolescents and 36 adults) completed a free kick training program for which attentional focus (internal vs. external) was manipulated. Results indicated that the external focus group showed greater improvements compared to the internal focus group. These findings therefore provide further support for the advantages of external focus of attention instructions during skill acquisition and further show that this remains true for prolonged training periods. Das Ziel dieser Studie war es zu untersuchen, ob ein Fußball-Freistoßtraining die Flatterball-Technik von jugendlichen und erwachsenen Fußballspielern nach einer dreiwöchigen Intervention verbessert. Dabei wurden entweder internale oder externale Aufmerksamkeitsanweisungen verwendet. Vergangene Studien zeigen, dass ein externaler Aufmerksamkeitsfokus effektiver ist als ein internaler Aufmerksamkeitsfokus während des Lernens. In der vorliegenden Studie absolvierten 56 Fußballspieler (20 Jugendliche und 36 Erwachsene) ein Freistoß-Trainingsprogramm, bei dem der Aufmerksamkeitsfokus (internal oder external) manipuliert wurde. Die Ergebnisse zeigten, dass die externale Fokusgruppe größere Verbesserungen im Vergleich zur internalen Fokusgruppe zeigte. Diese Ergebnisse unterstützen daher die Vorteile externaler Aufmerksamkeitsanweisungen während des Fertigkeit-Erwerbs, auch bei längeren Interventionen.